1994
DOI: 10.1288/00005537-199409000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of basic fibroblast growth factor in tympanic membrane repair

Abstract: Basic fibroblast growth factor (bFGF) has been shown to enhance speed of wound repair at a number of anatomic sites. This study presents an evaluation of bFGF in a model of acute tympanic membrane (TM) perforation in order to assess rate of healing as well as structural and functional outcome. Perforations were created in the tympanic membranes of rats, then allowed to heal in the presence of topically applied bFGF with the opposite ear serving as a control. The growth factor was applied in repeated doses begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 14 publications
3
39
1
2
Order By: Relevance
“…Estudos realizados nas duas últimas décadas apontam a importância de fatores de crescimento próprios da membrana timpânica normal e a expressão destes fatores ocorrendo de forma diferente em membranas timpânicas perfuradas [23][24][25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estudos realizados nas duas últimas décadas apontam a importância de fatores de crescimento próprios da membrana timpânica normal e a expressão destes fatores ocorrendo de forma diferente em membranas timpânicas perfuradas [23][24][25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Discussionunclassified
“…A aquisição desses fatores de crescimento é possível por técnica de DNA recombinante que é complexa [21][22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Introductionunclassified
“…Such therapeutic effects of bFGF are also seen when it is applied exogenously. Furthermore, bFGF effectively increases the healing of TM perforations in guinea pigs [10][11][12] , rats [13][14][15] , and chinchillas [16] . These clinical and experimental results suggest that bFGF affects the healing of TM perforation.…”
Section: Discussionmentioning
confidence: 97%
“…Orientation of the fibroblast is already underway (Mondain et al 1991). Another study showed treated TMs healed on average 4 days earlier than control TMs (Vrabec et al 1994). Further studies showed no significant difference in healing time (Chauvin et al 1999;Friedman et al 1997).…”
Section: Fgf2mentioning
confidence: 99%
“…There are several studies examining the role of FGF2 application to the acutely healing tympanic membrane (TM) (Mondain and Ryan 1994;Fina et al 1991;Fina et al 1993;Mondain et al 1991;Vrabec et al 1994). Research suggests that only high doses have a significant effect but these effects were counterbalanced by the effects of a hypertrophic wound, possibly due to the gelfoam TM used for application (Mondain et al 1991).…”
Section: Introductionmentioning
confidence: 99%